The quality of caregiver–child interactions in infant classrooms in Portugal: the role of caregiver education - Barros, Sílvia (2017)
Recent research has shown that caregiver education and training can be important in determining levels of quality in early childhood, but has mainly considered the education and training of the lead teacher. In infant child care, however, classrooms have more than one caregiver with varying levels of education and in Portugal it is less common to have a qualified teacher exclusively assigned to infant classrooms. This study examines the quality of caregiver–child interactions in infant classrooms and its association with caregiver qualifications and training, specifically the level of pre-service education and in-service training of the lead caregiver, whether she is exclusively assigned to an infant classroom or to more classrooms, and the pre-service education of the multiple caregivers in the classroom. Participants were 90 infant classrooms from Porto, Portugal. The CLASS–Infant was used to measure quality of caregiver–infant interactions. Classrooms with one lead caregiver holding at least a bachelor’s degree, whether exclusively assigned to the infant classroom or not, showed higher levels of quality. Few effects were found for in-service training. Results suggest that lead teachers with pre-service education in early childhood are likely to play an important role not only directly by interacting with children but also indirectly through team work.